Overvaluation of weight and shape in obesity: a comparative study between people with and without binge eating disorder - Escandón-Nagel, Neli; Peró-Cebollero, Maribel; Grau, Antoni; Soriano, José; Feixas, Guillem (Frontiers in Psychology, 2024)
Introduction: The overvaluation of weight and shape is a diagnostic criterion in eating disorders, except in binge eating disorder (BED), where it has received less attention. This aspect is also not usually analyzed in people with overweight or obesity without an eating disorder. This research aims to identify the indicators of symptomatology, as well as those of self-construction and cognitive structure, that are associated with overvaluation in obesity, either alone or in conjunction with BED.Method: A sample of 102 overweight or obese participants was accessed. The sample was divided into four groups: one without overvaluation or BED (n = 33); a second with overvaluation and without BED (n = 21); a third with BED, but without overvaluation (n = 15), and a fourth with BED and overvaluation (n = 33). The groups completed instruments regarding eating symptomatology, anxiety, depression, and stress. In addition, they were administered the Repertory Grid Technique, a semi-structured interview to evaluate the cognitive structure involved in the construal of the self and others. Results: The factors of overvaluation and the presence of BED independently explained eating symptomatology, and the latter also showed a tendency to influence anxiety, depression, and stress. In terms of cognitive structure, weight polarization was explained by overvaluation, while BED was associated with a high presence of cognitive conflicts. In self-construction, BED was the factor that explained the differences, particularly in Self-Ideal discrepancy. Discussion: The results highlight the importance of overvaluation in obesity, even in the absence of BED. Its evaluation and treatment are recommended. Furthermore, in the case of BED, it is also advisable to evaluate the overvaluation of weight and shape since it can be a severity specifier.